THE EFFECT OF EXPERIENTIAL MARKETING, PRODUCT QUALITY, STORE ATMOSPHERE, AND SERVICE QUALITY ON CUSTOMER LOYALTY - Zahruna, Ulfi; Feti Fatimah; Yohanes Gunawan Wibowo (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to analyze the influence of Experiential Marketing, Product Quality, Store Atmosphere, and Service Quality on customer loyalty at Kopixel Jember. The background to this research is the importance of maintaining customer loyalty in the increasingly competitive coffee shop industry. Method: This research uses a quantitative approach with a survey method through questionnaires distributed to 220 respondents who are Kopixel customers. Data were analyzed using multiple linear regression to test the influence of each independent variable on customer loyalty. Results: The research results show that the four variables have a positive and significant influence on customer loyalty. Experiential Marketing has a regression coefficient of 0.321, Product Quality of 0.284, Store Atmosphere of 0.295, and Service Quality of 0.312. The Product Quality variable has a dominant influence, showing the importance of product quality in creating customer satisfaction and loyalty. Novelty: This research provides practical contributions for Kopixel managers and can be a reference for similar research in the future. Kopixel is advised to focus on product innovation, facility improvements, and employee training to create a better customer experience.